The Effect of Stretching and Strengthening Exercises on Reducing Pain and Functional Disorders in Subacromial Pain Syndrome: A Literature Review - Wahyuni, Wahyuni; Randa, Meybi (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Shoulder pain is the third most common pain in musculoskeletal cases, after lower back and knee pain. These complaints are caused by various things, including subacromial pain syndrome. Subacromial pain syndrome is a synonym for rotator cuff syndrome, which refers to all non-traumatic unilateral shoulder problems involving the structures surrounding the subacromial. The purpose of this study was to determine the effect of stretching and strengthening exercises on reducing pain and functional impairment in subacromial pain syndrome. Methods: The method used is a literature review with a narrative type. The data for the selected publication articles are RCTs for 2013-2022 in English. Search publication articles using search PEDro, and Google Scholar which are classified into inclusion and exclusion criteria. Data analysis by assessing the quality of journals using the PEDro scale, outline literature review of the PICO method and data synthesis. Results: Strengthening and stretching exercises show significant short-term functional improvement and pain reduction in subacromial pain syndrome. Additionally, specific rotator cuff and scapular exercises, combined with active/passive ROM exercises, significantly enhance function and reduce pain levels. Conclusion: Strengthening (eccentric, isometric) and stretching exercises on the posterior shoulder and rotator cuff or scapular in the short term have an effect on reducing pain (VAS), as well as a significant improvement in function (DASH scale).